P107 Time to re-group: a novel approach to the delivery of speech and language therapy for chronic refractory cough. (15th November 2017) - Selby, J; Bailey, E; Gillies, F; Hull, JH
Abstract : Introduction: Specialist speech and language therapy (SLT) has an important role in the treatment of chronic refractory cough (CRC). Therapy is typically delivered to patients individually; however, this approach is resource-intensive and reduces service capacity. Moreover, the content of SLT for CRC is often similar across patients. The aim of this work was to describe the efficacy of a SLT-delivered cough therapy group (CTG). Methodology: Eligible patients attended the CTG (2016–2017) after an initial 1:1 assessment to determine suitability. Individuals with an infectious cause of cough were excluded. All patients had undergone prior assessment and treatment optimisation at the RBH chronic cough clinic. Cough severity was rated using a visual analogue scale (VAS) at first attendance and on discharge from the group. Patients attended a maximum of four sessions with 4–8 patients per session, after which they were referred for individual review if they felt no improvement had been made. CTG sessions consisted of strategies to reduce cough frequency (through improved upper airway lubrication, reduction of laryngeal muscle strain and use of cough control strategies), sharing experiences, observing other patient-therapist interactions and time to talk individually with the SLT. Results: Ninety-one patients (n=26 males, 28.6%) aged between 30 and 83 years ( M =61.4, SD 11.1) attended CTG. The majority of attendees (n = 46, 50.5%) reported cough duration of greater than 15 years. There was a reduction in mean VAS following group attendance (p < 0.05 ) (figure 1 ) with the greatest reduction noted after 3 attendances (p < 0.05 ) . The most common patient-reported benefits of group attendance were sharing advice (80.2%) and meeting other people with a cough (76.9%). Conclusion: A group-delivered SLT treatment intervention was associated with reduction in cough severity in a cohort of patients with CRC. Service benefits included reduced waiting time and improved access to individual SLT sessions. Future work should focus on qualitative analysis of patient-reported benefits of group therapy and evaluation of efficacy in a prospective, randomised study.